More is not always better: longitudinal associations and nonlinear dose–response relationships between physical activity, psychological capital, and positive body image among Chinese university students - Yi Li; Xi Chen (Frontiers in Public Health, 2026)
Objective This study examined the longitudinal associations between physical activity (PA), psychological capital (PsyCap), and positive body image, operationalized as body appreciation, among Chinese university students. We further evaluated the mediating role of PsyCap and explored potential nonlinear dose–response relationships between different dimensions of PA and body appreciation. Methods A two-wave longitudinal survey with a three-month interval was conducted among 669 university students from four universities in Z City, China. PA was assessed using the Physical Activity Rating Scale-3 (PARS-3), PsyCap was measured using the Psychological Capital Questionnaire-24 (PCQ-24), and body appreciation was assessed using the Body Appreciation Scale-2 (BAS-2). Cross-lagged panel models were used to examine prospective associations, longitudinal mediation was evaluated using bias-corrected bootstrap procedures, and polynomial regression models were fitted to investigate nonlinear dose–response relationships. Results Male students reported significantly higher levels of PA, PsyCap, and body appreciation than female students (all p < 0.05). Baseline PA prospectively predicted higher PsyCap ( β = 0.121, p < 0.001) and greater body appreciation ( β = 0.264, p < 0.001) at follow-up, whereas baseline PsyCap also predicted subsequent body appreciation ( β = 0.170, p < 0.001). Exercise intensity was linearly associated with PsyCap, whereas exercise duration and frequency exhibited U-shaped associations. For body appreciation, exercise intensity and frequency showed positive linear associations, whereas exercise duration demonstrated a significant cubic nonlinear association with body appreciation. Longitudinal mediation analysis indicated that PsyCap partially mediated the prospective association between baseline PA and follow-up body appreciation, accounting for 23.33% of the total association. Conclusion Higher levels of PA were prospectively associated with greater PsyCap and body appreciation among Chinese university students. PsyCap partially accounted for the statistical covariation in the prospective association between PA and body appreciation. Different dimensions of PA demonstrated distinct dose–response patterns, suggesting that the psychological benefits of PA may vary according to exercise intensity, duration, and frequency. These findings indicate prospective temporal associations.